MAKAN DAN MINUM BERDIRI DALAM HADIS AL-KUTŪBUSSITTAH DAN IMPLEMENTASINYA PADA SANTRI PESANTREN - Randi Fidayanto (LPPM AMIK Citra Buana Indonesia, 2018)
The attitude of eating and drinking while sitting has been rooted since childhood in society. So it raises a tough attitudetowards others different from the attitude. Radical tendencies that tend to be radical are very dangerous for proper religious practice. The search for the attitude of eating and drinking in the hadith al-Kutūbussittah is necessary to know the law of eating and drinking while standing real. Therefore it is necessary to know the extent to which the implementation of hadiths of eating and drinking while standing in the environment of santri. The subject of this research is studentsof class XII SMA Al-Minhaj Ma'had Minhaj Shahabah Tamansari Bogor. Research is a qualitative research that focuses on the problem of how to eat and drink attitude in Hadith al-Kutūbussittah and whether impelementasinya eat and drinkstanding at santri class XII Ma'had Minhaj Shahabah Bogor and how the interaction of understanding students with theimplementation of Hadiths of eating and drinking while standing. The approach used in this research is the normative theological approach with the field research design combined with the literature research. The data collection is done by the researcher himself by way of; (1) closed questionnaire;(2) observation; And (3) documentation study. For data analysis using descriptive technique that its application is done in three activity flow, that is data reduction, data presentation, and conclusion or verification. To know the credibility of data, done with triangulation technique. The results showed that first, In al-Kutūbussittah mentioned attitudes related to eating and drinking in some form: the prohibition of eating and drinking while standing, may eat and drink while standing, the attitude of eating with al-iq'a, the ban on eating while leaning, And may eat and drink while walking either implicitly or explicitly. Second, Santri class XII SMA Al-Minhaj Tamansari Bogor implements the hadith ban on eating and drinking while standing alone and not apply the traditions of eating anddrinking while standing and walking. Hadiths may eat and drink while standing and walking is not applied because of theignorance of the hadiths. Thirdly, the Ignorance shapes their understanding of eating and drinking while standing andwalking. Understanding is practiced so that it becomes a habit. These habits form an imprecise attitude to their different practices. From the research results can be suggested (1) Implementing improvements in the way of teaching pesantren in teaching the hadiths of the Prophet integrally on a problem is not partial so as to make a complete understanding of santri; (2) Increasing the study of muqaranah fiqh to eliminate khilafiyyah fiqhiyyah gap on Muslims; (3) To popularize the study ofhadith al-kutūbussittah for Muslims so that they better understand the teachings of Islam from the main source.